Local Wisdom-Based Democracy: A Fiqh Siyasah Analysis of the Gilir Kaum System in the Village Head Election in Sibak Village, Bengkulu - Fauzan Fauzan; Toha Andiko; Ade Kosasih; Rohmadi Rohmadi; Ismail Jalili; Miinuddin Miinuddin (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This study examines the practice of democracy based on local wisdom through the gilir kaum system in village head elections among the Pekal community of Sibak Village, Mukomuko, from the perspective of fiqh siyasah. The gilir kaum system is a rotational leadership mechanism among clans designed to ensure equitable power distribution, prevent conflicts, and maintain social harmony. The research applies a qualitative-descriptive approach with normative-empirical analysis, using in-depth interviews, field observations, and the review of customary documents and village regulations. The findings show that the gilir kaum system plays an essential role in maintaining political stability, strengthening community participation, and reflecting tradition-based democracy. It also integrates modern democratic values with local wisdom. Leadership rotation ensures fair power distribution, while direct voting provides space for public participation in accordance with Law No. 6 of 2014 on Villages. From the perspective of fiqh siyasah, the gilir kaum system holds legitimacy as long as it upholds justice (‘adl), consultation (syura), and public interest (maslahah). Thus, it represents an adaptive model of local democracy in Indonesia, integrating tradition, modern democracy, and Islamic values